First molecular assessment on Cosmocerca spp. from Brazilian anurans and description of a new species of Cosmocerca (Ascaridomorpha: Cosmocercoidea) from the white-spotted humming frog Chiasmocleis albopunctata (Boettger, 1885) (Anura: Microhylidae) - Alcantara, E. P. [UNESP]; Ebert, M. B. [UNESP]; Müller, M. I.; Úngari, L. P. [UNESP]; Ferreira-Silva, C. [UNESP]; Emmerich, E. [UNESP]; Santos, A. L.Q.; O'Dwyer, L. H. [UNESP]; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2022)
Cosmocerca spp. are common nematode parasites of amphibians. We provide herein molecular data for two species of Cosmocerca and describe a new species, Cosmocerca albopunctata n. sp., using light microscopy and molecular data (cytochrome c oxidase subunit 1-COI mtDNA). Cosmocerca albopunctata n. sp. can be easily distinguished from other congeneric species by the combination of characteristics such as body size, length of spicules and gubernaculum, and the arrangements and number of caudal papillae (7 + 1:1 + 1:6). The phylogenetic results based on the partial COI mtDNA sequences clustered the new species in a monophyletic clade along with the other sequences of Cosmocerca spp. Therefore, our results contribute to the knowledge about the species diversity and genetic data for Cosmocerca spp. in the Neotropical region.
Keywords: Anura; Cosmocercidae; molecular identification; morphology; Nematoda